Design and Code Reviews in the Age of the Internet. - MEYER, BERTRAND (Communications of the ACM, 2008)
The article discusses computer software and code reviews, describing the advanced tools that allow software-development teams that are located around the world to collaborate on projects. The author indicates that such a team format turned out to be beneficial. Topics include communication threads occurring in parallel, emphasis on the written dialogue over verbal discussion, and completing much of the review before the meeting itself. Also discussed are 'code inspections,' finding programming flaws, and uncovering deficiencies.